Diseño plan de mejoramiento apertura de D’ Orden para las importaciones en la agencia de aduanas Agecoldex SA Nivel 1 (2023)
Customs agencies in Colombia aim to collaborate with customs authorities in the application of legal regulations related to foreign trade, this ranges from customs agency which means making the process of importing and exporting goods easier and faster; To achieve this, it is very important to stay up to date with all customs regulations and venture into technology.